Tribunal de Contas na Constituição de 1988: controle social e accountability - Faria, Nádia Rezende (2013)
Social control is an essential instrument in the democratic state of law, because it can make possible the exercise of fundamental principles, such as citizen participation and public patrimony defense. The Brazilian Constitution of 1988 assigned many instruments of popular participation in order to ensure public control by society itself, including denunciation before the Court of Auditors, which can be held by any citizen, political party, association or syndicate, according to art. 74, §2º of the Constitution of 1988. This constitutional institute opens a prolific way for the discussion about the role of Court of Auditors, not only as an auxiliary organ of Legislative power, but also as an organ which defends constitutional principles, fundamental rights, and democracy itself. Then, this work is an investigative bibliographic research which principal aim is to analyze if the Brazilian Court of Auditors should be considered, after the Constitution of 1988, also an instrument of vertical accountability, although within the term of Political Science it is only presented as an instrument of horizontal accountability. Also, this study is due to analyze, beyond the formal aspect, some actions and programs hold by the Courts around Brazil in order to present the social efficacy of the control undertaken by society and the Courts of Auditors together.